Characterisation of polyphenol oxidase and peroxidase and the role in browning of loquat fruit - Xinglong ZHANG; Xingfeng SHAO (Czech Journal of Food Sciences, 2015)
Polyphenol oxidase (PPO) and peroxidase (POD) were extracted from a new loquat fruit cultivar (Ninghaibai) and characterised using reliable spectrophotometric methods. In both cases, the optimum pH for PPO was 4.5 and 5 for POD, and their optimum temperatures were 30 and 35°C, respectively. Both enzymes followed Michaelis-Menten kinetics, showing Km= 47.11 mmol/l for PPO with catechol as the substrate and Km = 153.00 mmol/l for POD with guaiacol as the substrate. PPO was much more thermolabile than POD, losing more than 40% of relative activity after 30 min of heating at 40°C. PPO activation energy was much lower than POD activation energy (ΔE# = 39.74 and 94.65 kJ/mol for PPO and POD, respectively): Both enzymes activities showed decreasing patterns as the compound concentration in the assay medium increased. 4-hexylresorcinol (4-HR), oxalic acid, and l-cysteine showed strongly inhibitive effects on the enzymes. Changes in L*, a*, and b* values were chosen to describe the browning of loquat pulp. Only PPO displayed a higher negative correlation with L* values, which indicated that PPO plays an important role in the browning of stored loquat cv. Ninghaibai.